Pengaruh Debt Financing dan Equity Financing Terhadap Profit Expense Ratio Pada Bank Umum Syariah di Indonesia Periode - Indrayani Indrayani; Murhaban Murhaban (SI-MEN, 2019)
This study aims to determine the effect of Debt Financing and Equity Financing on the Profit Expense Ratio of Islamic commercial banks operating in Indonesia in 2014-2016 partially. The data used in this study are quantitative data in the form of secondary data in the form of annual financial statements during 2014-2016 with 36 observations. The sample in this study are all Islamic commercial banks in Indonesia, which amounted to 13 banks and the samples in this study are 12 Islamic commercial banks selected by purposive sampling method. The data analysis method used is multiple linear regression. The results of the study show that (1) Debt Financing has a positive and significant effect on Profit Expense Ratio in Islamic commercial banks in Indonesia. (2). Equity Financing has a positive and significant effect on Profit Expense Ratio in the Islamic commercial banks in Indonesia.